The Role of Physical Exercise in Food Intake Suppression - Sari, Widia; Kartinah, Neng Tine (Universitas Baiturrahmah, 2024)
Obesity is a global health issue since it is related to diseases that are the leading causes of mortality, such as diabetes, stroke, and cardiovascular disease. A long-term imbalance between energy intake and energy expenditure is one of the factors contributing to obesity. In addition to increasing energy expenditure, physical exercise can also aid in weight loss by decreasing food intake. An increase in appetite-regulating hormones (ghrelin, GLP-1, leptin, and adiponectin), myokines (IL-6 and irisin), and lactate mediates the suppression of food intake during physical exercise. These substances function as signals that regulate food intake at the peripheral and/or central nervous system levels. Peripherally, lactate inhibits ghrelin secretion, while IL-6 increases GLP-1 secretion. In the center for regulating food intake, lactate, IL-6, leptin, and adiponectin act by inhibiting the release of orexigenic neuropeptides (NPY/AgRP) and increasing the release of anorexigenic neuropeptides (POMC). This review highlighted the role of physical exercise in overcoming obesity through suppression of food intake mediated by hormones and myokine changes that play a role in regulating food intake either in the periphery or directly in the central nervous system.